Burden and determinants of undernutrition among young pregnant women in Ethiopia. Issue 3 (11th December 2018) - Workicho, Abdulhalik; Belachew, Tefera; Ghosh, Shibani; Kershaw, Meghan; Lachat, Carl; Kolsteren, Patrick
Abstract: Undernutrition is a major public health concern due to its association with the mortality and disease burden of women and children. This study aimed at identifying the extent and determinants of undernutrition among young pregnant women in Ethiopia. A multivariable regression analysis was fitted to identify determinants of undernutrition and anaemia in a sample of 1, 393 pregnant women. Risk ratios (RRs) with 95% confidence interval (CI) were estimated. All the analyses were performed using STATA version 14 and adjusted for clustering. The study revealed that 38% of the women were undernourished and 22% were anaemic. Improved maternal education, RR = 0.94, 95% CI [0.89, 0.98]; higher wealth status, RR = 0.72, 95% CI [0.47, 0.95]; higher minimum dietary diversity for women, RR = 0.87, 95% CI [0.77, 0.98]; increased maternal height, RR = 0.96, 95% CI [0.94, 0.98]; and protected water source, RR = 0.93, 95% CI [0.86, 0.96], have decreased the risk of undernutrition while using unimproved toilet, RR = 1.31, 95% CI [1.06, 1.63], and depression, RR = 1.33, 95% CI [1.14, 1.55], increased the risk of anaemia. Animal source food consumption decreased both the risk of undernutrition, RR = 0.85, 95% CI [0.77, 0.94], and anaemia, RR = 0.91, 95% CI [0.85, 0.95]. The burden of undernutrition is still high. Although improved socio‐economic status and dietary practices decreased the risk of undernutrition, poor health and environmental conditions were still significant risk factors. These findings suggest the need to target this set of important determinants to significantly decrease the burden of undernutrition among young pregnant women.